Schur Harmonıc Convexıty of Related Functıon for Holders Inequalıty wıth Applıcatıon - Sreenivasa Reddy Perla , S. Padmanabhan (International Journal of Advanced Science and Technology, 2020)
In this paper, make use of majorization inequality theory investigated the Schur harmonically convex regarding related function of Holders Inequality, giving a complete essential condition of Schur harmonically convex function to Holders Inequality and some applications are established.